Preoxygenation in surgical patients undergoing general anaesthesia – A cross sectional survey - Jangda, Iqra; Gauhar Afshan (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency of preoxygenation practice among anaesthesiologists, the reason for skipping preoxygenation, and the endpoint chosen to stop preoxygenation. Method: The prospective, cross-sectional study was conducted from April to September 2018 at the Department of Anaesthesiology, Aga Khan University, Karachi, and comprised anaesthesiologists with at least two years of experience. Data regarding preoxygenation practice was collected through structured interviews. Data was analysed using SPSS 19. Results: Of the 76 subjects, 43(56.6%) were females and 33(43.4%) were males. The overall mean age was 35.1±7.4 years. A total of 30(39.5%) sujects performed preoxygenation in all elective surgical patients undergoing general anaesthesia. The most common instance for not performing preoxygenation was healthy adults and anxious patients in 19(41.3%) cases. The technique most preferred was tidal volume breathing for 3-5 minutes 34(44.74%). Four deep breaths in 30 seconds were used by 25(32.89%) anaesthesiologists, and the technique least preferred was 8 deep breaths in 1 minute by 17(22.37%). Besides, 69(90.8%) anaesthesiologists chose to end tidal oxygen at >90% as their endpoint of preoxygenation, and 7(9.2%) performed it for three minutes. Conclusion: The standard technique to perform preoxygenation was found to be the most preferred technique used by anaesthesiologists. The preoxygenation was skipped mainly in young healthy and anxious adults. The endpoint chosen by anaesthesiologists was almost always the end tidal oxygen >90%. Key Words: Pre-oxygenation, De-nitrogenation, Practice, Endpoint, Anaesthetist.